2017
DOI: 10.1051/parasite/2017044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thein vitroanthelmintic effects ofAcacia niloticaandAcacia raddiana

Abstract: Gastrointestinal nematodes are a major threat to small ruminant rearing in the Sahel area, where farmers traditionally use bioactive plants to control these worms, including Acacia nilotica and Acacia raddiana. The main aim of this study was to screen the potential anthelmintic properties of aqueous and acetone extracts of leaves of these two plants based on three in vitro assays: (1) the egg hatch inhibition assay (EHA); (2) the larvae exsheathment inhibition assay (LEIA) using Haemonchus contortus as a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…Erica cinera was more active against eggs and L 3 of T. columbriformis than to inhibit the egg hatching and larvae exsheathment of abomasal parasites ( H. contortus and T. circumcinta ) (Moreno-Gonzalo et al ., 2013 a , 2013 b ). The Agave sisalana and Moringa oleifera has greater ovicidal effect while Acacia nilotica and A. raddiana are more active against L 3 of GIN (Botura et al ., 2013; Zabré et al ., 2017; De Medeiros et al ., 2018). These variations can be related with differences in various enzymatic constituents and membrane structures of the species and nematodes' life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Erica cinera was more active against eggs and L 3 of T. columbriformis than to inhibit the egg hatching and larvae exsheathment of abomasal parasites ( H. contortus and T. circumcinta ) (Moreno-Gonzalo et al ., 2013 a , 2013 b ). The Agave sisalana and Moringa oleifera has greater ovicidal effect while Acacia nilotica and A. raddiana are more active against L 3 of GIN (Botura et al ., 2013; Zabré et al ., 2017; De Medeiros et al ., 2018). These variations can be related with differences in various enzymatic constituents and membrane structures of the species and nematodes' life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ngaradoum et al (21) showed that methanolic extract of Ziziphus mucronata barks has a significantly (p<0.05) higher activity with an inhibition concentration 50 (IC 50 ) value of 3.9 mg/mL than AE with an IC 50 value of 14.7 mg/mL when tested against Haemonchus contortus egg. In addition, Zabré et al (22) reported that Acacia raddiana is effective with IC 50 =1.58 mg/mL for AE and IC 50 =0.58 mg/mL for acetonic extract for egg hatch inhibition. These differences may be attributed to the used concentration and the composition of plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…coronopus, which was more active against larvae exsheathment (IC 50 = 94.0 and 212.4 µg mL − 1 ), and inactive towards eggs, of both parasite species, at the maximum concentration tested. Overall, IC 50 results obtained in LEIA are frequently reported as lower than EHA, suggesting that infective L3 larvae are more susceptible than eggs [36,37].…”
Section: In Vitro Anthelmintic Propertiesmentioning
confidence: 99%